Information and Communication Technology (ICT) and Economic Growth in Malaysia - Jee, Sau Rong; Nur Nadhira, Baharuddin; Rossazana, Ab. Rahim (Human Resource Management Academic Research, 2020)
This study aims to examine the impact of information and communication technology (ICT) on economic growth in Malaysia. The motivation of this study is to estimates the impact of ICT advancement towards the performance of the Gross Domestic Product (GDP) in Malaysia. The domestic GDP is selected as the dependent variables while the labour force participation, the contribution of ICT, the mobile cellular subscriptions and the individual usage of internet are utilised as the independent variables for this study. The time-series data collected for this study is for the period of 25 years, which is from the year 1994 until year 2018. The data set is then being further tested by using the unit root test which includes the Augmented Dickey-Fuller (ADF) test and the Kwiatkowski-Philip-Schmidt-Shin (KPSS) test. Meanwhile, estimating the cointegration and relationship between the variables will tested using the Johansen and Juselius (J&J) Cointegration Test, the Vector Error Correlation Model (VECM) and the ranger Causality test. Based on the result of this study, the mobile cellular subscriptions and individual usage of internet are estimated to have a significant and positive relationship with the Gross Domestic Product (GDP) in Malaysia. The findings of this study show that the contribution of Information and Communication Technologies (ICT) assist to enhance the Gross Domestic Product (GDP) of Malaysia. The estimations from this study hopefully will support the active role played by the government in creating the network society by prioritizing the policies that will become the enablers in the advancement of ICT environment in the country and eventually support the economic growth of Malaysia.